Design of Management Model for Facilitating Practice of Schooling Field Introduction - Hartutik, Hartutik; Setiyaningtiyas, Nerita; Stella Pradnya, Matilda; Nindita Pradnya, Irene (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2023)
This study explores the enhancement of teacher quality and its impact on learning outcomes. It emphasizes the significance of professional competency development among educators. The study focuses on pre-service training as a means to improve the quality of prospective teachers. The study introduces a four-stage experiential learning cycle—real experience, reflective observation, abstract conceptualization, and active experience—tailored for prospective teachers. The study's primary objective is to elucidate the management model of mentoring and the implementation of schooling introduction within the context of Santo Fransiskus Assisi Semarang Pastoral and Catechetical College. Employing a qualitative research approach, the researchers investigate the experiences of practice assistants involved in Introduction to Schooling Fields (PLP) through interviews and observations. Informants are selected through purposive sampling. Data collection encompasses interviews, observations, and documentation methods guided by predefined interview guidelines. Concurrently, the activities of accompanying lecturers are observed to ensure effective PLP preparation for students. The collected data undergoes content analysis, leading to the identification of themes for subsequent focus group discussions (FGD). The FGD deliberates on pertinent methods for assisting the PLP practice of prospective Catholic religious education teachers. The study culminates in the design of a mentoring model for future PLP practices. Notably, the research emphasizes qualitative interpretation over quantitative frequency in data analysis. Ultimately, the study advocates for the practical application of acquired knowledge in real teaching scenarios under the guidance of adept mentors, enabling students to refine their skills and enrich their understanding through experiential teaching.